The Influence of Money Politics on Publics Participation in The 2024 Regional Election - Fadiana Fadiana; Bahagia Bahagia (PT Riset Mandiri Nusantara, 2025)
Regional Head Elections (Pilkada) are one manifestation of democratic governance in Indonesia, providing the public with the opportunity to elect their regional leaders directly. However, the practice of money politics continues to threaten the integrity of elections, including in Banda Aceh City. This research is motivated by the high Human Development Index and education level in Banda Aceh, which have not been fully effective in suppressing money politics during the 2024 Pilkada. The objective of this study is to analyze the influence of money politics on community participation in the 2024 Pilkada in Banda Aceh City. This research employs Edward Aspinal’s theory of money politics and the theory of political participation as its conceptual foundation. The research uses a quantitative approach, employing a survey method via the distribution of questionnaires to 322 respondents selected using the Slovin formula. The collected data were analyzed using validity and reliability tests, simple linear regression, and t-tests. The results indicate that money politics influences community participation, though its contribution is relatively small, with an R² of 35%. This finding suggests that money politics still affects voting behavior, even as some members of the community have begun to show greater political awareness. Based on the results, this study emphasizes the need for election organizers and supervisory bodies to strengthen political education. It encourages political parties to conduct more ethical, transparent, and accountable campaigns, thereby further improving the quality of democracy at the local level.